Syphilis Acquired in Brazil: Retrospective analysis of a decade (2010 to 2020) (Research, Society and Development, 2021)
This study had a propose of carrying out a critical evaluation of the available data on syphilis acquired in the Information System for Notifiable Diseases (SINAN), in the period from 2010 to 2020. It was verified that until the year 2018, there was an annual increase in the registration of syphilis cases, with a decrease in the number of cases in 2019 and 2020. In 2020 there was a reduction equivalent to 1/3 of the total records, compared to the previous year, probably under-reporting due to Covid-19 pandemic. 2018 was the year with the highest number of reported cases and the highest detection rate (76.2 cases per 100 thousand inhabitants), with the detection rate for that year in the southeast region (82.5) surpassing the national one. The male gender was more affected than the female, due the risk behavior of men, however, with an increasing increase of infection also in women, due to the stability of the relationship, without use of the condom. More developed and populous regions had the highest number of case reports. Although syphilis is easily treatable, with penicillin administration, it still remains a Brazilian public health problem, requiring more attention from health authorities, with greater investment in campaigns to prevent sexually transmitted infections. These, in turn, can be easily prevented with the use of condoms, which are distributed free of charge by the Ministry of Health. In addition, it is important to spread the complications that syphilis can cause when not treated, causing its evolution, as a warning resource for the population.